(untitled) (SASI, 2017)
The presence of MEA will be an economic area with a high level of competition and high, also a big threat associated with IPR that will be experienced by creative industries of Small and Medium Enterprises (MSME’s). The growing growth of MSME’s over the last 5 years has become the main capital for Indonesia in increasing domestic income. To provide intellectual property rights protection for creative industries of domestic MSMEs, especially in the field of Brand in welcoming the economy of ASEAN people with the presence of overseas products circulating in Indonesia, will give the opportunity for the similarity of the brand both products and services, it is necessary attention / the firmness of the government in protecting the products of the small domestic creative industry because the small industry is still lulled and still lay with the importance of registration of HKI on its brand products. Generally they are satisfied with the achievements of products and brands that are built acceptable to consumers regardless of whether their products will be imitated or hijacked.